Analisis Implementasi Corporate Social Responsibility dan Intensitas Research and Development pada Perusahaan Go-publik - Adi Santoso (Islamic Economics Journal, 2016)
The aim of this research is to examine and analyze the effect of Corporate Social Responsibility (CSR) and intensity of Research and Development (R&D), which is expected to improve firm value and stock return on companies that go public on the Indonesia Stock Exchange. The populations of this research are companies go public on the Indonesia Stock Exchange. The samples of this research 25 companies that go public, which are observed at 2010, 2011, and 2012. The results of this research generally indicate that (1) Corporate Social Responsibility (CSR) have a significant positive effect towards firm value, (2) Intensity of research and development (R&D) have a significant positive effect towards firm value, (3) firm value have a significant positive effect towards stock return, (4) foreign ownership is able to act as a moderating variable in raising corporate socialresponsibility (CSR) and firm value, (5) foreign ownership is not able to act as a moderating variable in raising intensity of research and development (R&D) and firm value.